Short- and Long-Term Effects of CBT-I in Groups for School-Age Children Suffering From Chronic Insomnia: The KiSS-Program. Issue 4 (4th July 2018) - Schlarb, Angelika A.; Bihlmaier, Isabel; Velten-Schurian, Kerstin; Poets, Christian F.; Hautzinger, Martin
ABSTRACT: Objective/Background: This intervention study evaluates the short- and long-term effects of cognitive behavior therapy for insomnia (CBT-I) in groups for school-age children and their parents, named the KiSS-program. CBT-I was implemented in three sessions for children and three sessions for parents. Participants and Methods: All in all, 112 children with chronic childhood insomnia were randomly assigned to a wait-list (WL) control or treatment condition. Results: According to subjective measures as well as objective wrist actigraphy, children in the CBT-I condition reported greater improvements in sleep behavior immediately after the treatment compared to the WL group. Improvements in sleep behavior after CBT-I persisted over the 3-, 6-, and 12-month follow-up assessments. Conclusions: The present study is the first randomized controlled trial that provides evidence for the long-term effectiveness of CBT-I in treating school-age children with chronic insomnia.